2010
DOI: 10.2147/copd.s12545
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and airflow limitation in chemical warfare patients with chronic obstructive pulmonary disease

Abstract: ObjectivesChronic obstructive pulmonary disease (COPD) is one of the main late complications of sulfur mustard poisoning. The aim of this study was to evaluate serum levels of interleukin (IL)-6 in war veterans with pulmonary complications of sulfur mustard poisoning and their correlation with severity of airways disease.MethodsFifty consecutive patients with sulfur mustard poisoning and stable COPD, and of mean age 46.3 ± 9.18 years were enrolled in this study. Thirty healthy men were selected as controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Specific alterations in circulating T-lymphocyte subpopulations and immunoglobulin subclasses have also been reported (Ghazanfari et al, 2013a, b). Serum levels of matrix metalloproteinase (MMP)s, elastase and IL-6 are also elevated, with levels directly correlating with the severity of pulmonary disease (Attaran et al, 2010; Kiani et al, 2013; Pourfarzam et al, 2013). Expression of inflammatory mediators including tumor necrosis factor (TNF)-α and IL-1β, as well as specific isoforms of TGF-β, are also chronically elevated in the lungs of SM exposed victims and related to the severity of symptoms (Yaraee et al, 2013; Zarin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specific alterations in circulating T-lymphocyte subpopulations and immunoglobulin subclasses have also been reported (Ghazanfari et al, 2013a, b). Serum levels of matrix metalloproteinase (MMP)s, elastase and IL-6 are also elevated, with levels directly correlating with the severity of pulmonary disease (Attaran et al, 2010; Kiani et al, 2013; Pourfarzam et al, 2013). Expression of inflammatory mediators including tumor necrosis factor (TNF)-α and IL-1β, as well as specific isoforms of TGF-β, are also chronically elevated in the lungs of SM exposed victims and related to the severity of symptoms (Yaraee et al, 2013; Zarin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, 48 , 49 COPD is not confined to the lungs and is a systemic inflammatory condition. 5 Fabri and Rabe suggested the term “chronic systemic inflammatory syndrome” to reflect the complexity of the condition.…”
Section: Assessment Of Symptomsmentioning
confidence: 86%
“…Interestingly, when the IL-6 level was highest at 4 h, the splenocyte apoptosis percentage of the SM group was not significantly different compared to the PG group; meanwhile, the necrosis percentage was also at the highest level. In vivo studies found that the serum IL-6 was increased in patients with sulfur mustard poisoning and COPD [ 48 ]. In vitro , treatment with 100 μmol/L of SM for 24 hours resulted in a significantly increased level of IL-6 secretion by human epidermal keratinocytes (HEKs) and human skin fibroblasts (HSFs) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with our finding that the IL-6 level increased after SM exposure. The main sources of IL-6 are monocytes, macrophages, T and B cells, fibroblasts, epithelial cells, and smooth muscle cells [ 48 ]. Therefore, we speculated that the gradual decrease in IL-6 was mainly due to the significant necrosis and apoptosis of T and B lymphocytes in the intoxicated spleen.…”
Section: Discussionmentioning
confidence: 99%